Assessing the itching intensity using visual analogue scales in atopic dermatitis patients against the background of a therapy with calcineurin inhibitors - V. V. Chikin; V. A. Smolyannikova; D. V. Proshutinskaya; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess the effect of topical treatment of atopic dermatitis patients with the 0.1% tacrolimus ointment on the itching intensity and skin expression level of growth factor proteins affecting the intensity of cutaneous innervation. Materials and methods. Fifteen patients suffering from atopic dermatitis underwent treatment with the 0.1% tacrolimus ointment. The SCORAD index was calculated to assess the severity of clinical manifestations. The itching intensity was assessed using a visual analogue scale. The skin expression of nerve growth factors, amphiregulin, semaphorin 3A and PGP9.5 protein (a nerve fiber marker) was assessed by the indirect immunofluorescence method. Results. An increased expression of the nerve growth factor and reduced semaphorin 3A expression levels were noted in the patients' epidermis; there was an increase in the quantity, mean length and fluorescence intensity of PGP9.5+ nerve fibers. As a result of the treatment, the disease severity and itching intensity were reduced, the nerve growth factor expression level was reduced while semaphorin 3A expression level increased in the epidermis, and the mean length and fluorescence intensity of PGP9.5+ nerve fibers was also reduced. A positive correlation among the itching intensity and nerve growth factor expression level, quantity and mean length of PGP9.5+ nerve fibers in the epidermis was revealed, and negative correlation between the itching intensity and semaphorin 3A expression level in the epidermis was established. Conclusion. Topical treatment with the 0.1% Tacrolimus ointment reduces the itching intensity in atopic dermatitis patients, which is related to the therapy-mediated reduction in the epidermis innervation level, decreased expression of epidermal nerve growth factor and increased semaphorin 3A expression level.